Saline-induced coronary hyperemia with continuous intracoronary thermodilution is mediated by intravascular hemolysis. (3rd October 2022) - Bertolone, D; Gallinoro, E; Candreva, A; Fernandez Peregrina, E; Bailleul, E; Meeus, P; Sonck, J; Bermpeis, K; Esposito, G; Paolisso, P; Heggermont, W; Adjedj, J; et al.
Abstract: Objectives: To test whether local hemolysis is a potential mechanism of saline-induced coronary hyperemia. Background: Absolute coronary flow can be measured by intracoronary continuous thermodilution of saline through the lateral side holes of a dedicated infusion cathete. A saline infusion rate at 15–20 mL/min induces an immediate, steady-state, maximal microvascular vasodilation. The mechanism of this hyperemic response remains unclear. Methods: Twelve patients undergoing left and right catheterization were included. The left coronary artery and the coronary sinus were selectively cannulated. Absolute resting and hyperemic coronary flow were measured by continuous intracoronary thermodilution. Arterial and venous samples were collected from the coronary artery and the coronary sinus in five phases: baseline (BL); resting flow measurement (Rest, saline infusion at 10 mL/min); hyperemia (Hyperemia, saline infusion at 20 mL/min); post-hyperemia (Post-Hyperemia, two minutes after the cessation of saline infusion); and control phase (Control, during infusion of saline through the guide catheter at 30 mL/min). Results: Hemolysis was visually detected only in the centrifugated venous blood samples collected during the Hyperemia phase. As compared to Rest, during Hyperemia both LDH (131.50±21.89 U/dL [Rest] and 258.33±57.40 U/dL [Hyperemia], p<0.001) and plasma free hemoglobin (PFHb, 4.92±3.82 mg/dL [Rest] and 108.42±46.58 mg/dL [Hyperemia], p<0.001) significantly increased in the coronary sinus. The percentage of hemolysis was significantly higher during the Hyperemia phase (0.04±0.02% [Rest] vs 0.89±0.34% [Hyperemia], p<0.001). Conclusions: Saline-induced hyperemia through a dedicated intracoronary infusion catheter is associated with hemolysis. Vasodilatory compounds released locally, like ATP, are likely ultimately responsible for localized microvascular vasodilation. Funding Acknowledgement: Type of funding sources: None.